Santiago Tobón “El privilegio, a veces, nos ciega” (2021)
He is not an office economist. He likes to be on the street talking with people, with policemen, with criminals, with ordinary citizens, because he knows that in order to understand the macro, one must know the micro. The winner of the Juan Luis Londoño de la Cuesta Medal award has built a path that reaffirms the importance of working for the well-being of others.